2016
DOI: 10.2174/1874210616021000069
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Post Bleaching Treatments in Stain Absorption and Microhardness

Abstract: Objectives:This study investigated the effects of post bleaching treatments to prevent restaining and the change of enamel surface microhardness after dental bleaching in vitro.Methods:Sixty intact human incisor teeth were stained in tea solution and randomly assigned into four groups (n=15). Then samples were bleached for two weeks (8 hours daily) by 15% carbamide peroxide. Tooth color was determined both with a spectrophotometer and visually before bleaching (T1) and immediately after bleaching (T2). Next, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…One possible factor that may have contributed to the reduction of enamel microhardness was the contact time of fluoride free bleaching gel with enamel surface which may have disrupted the balance between demineralization caused by the bleaching agent and the remineralization caused by artificial saliva. 27,33,34 These findings are in agreement with our SEM analyses, where was observed an irregular surface with depressions, porosity, and increased depth of enamel grooves. 13 Other studies also observed these alterations and the enamel microhardness decrease when low carbamide peroxide (10 or 15%) concentrations were used for long treatment times.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One possible factor that may have contributed to the reduction of enamel microhardness was the contact time of fluoride free bleaching gel with enamel surface which may have disrupted the balance between demineralization caused by the bleaching agent and the remineralization caused by artificial saliva. 27,33,34 These findings are in agreement with our SEM analyses, where was observed an irregular surface with depressions, porosity, and increased depth of enamel grooves. 13 Other studies also observed these alterations and the enamel microhardness decrease when low carbamide peroxide (10 or 15%) concentrations were used for long treatment times.…”
Section: Discussionsupporting
confidence: 89%
“…Several aspects related to bleaching agents might influence the enamel surface microhardness, such as peroxide concentration, time of application, pH or the incorporation of fluoride in bleaching agents. 25,[32][33][34][35] The bleaching agent used has a pH of 5.8 and this pH could not have contributed significantly to enamel demineralization. One possible factor that may have contributed to the reduction of enamel microhardness was the contact time of fluoride free bleaching gel with enamel surface which may have disrupted the balance between demineralization caused by the bleaching agent and the remineralization caused by artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an aqueous environment, this material undergoes a series of reactions, resulting in the formation of a surface layer made of hydroxy-apatite and/ or hydroxycarbonate apatite. (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) However, the remineralization potential of bioactive glass has so far not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of mechanical properties of enamel after the use of bleaching agents could be regained by the incorporation of agents that can compensate for the mineral loss ( 7 ). Several types of lasers, with different parameter settings, have been used for enamel reinforcement ( 8 ). The CO2 laser (9.3, 9.6, 10.3 and 10.6 μ wavelengths), however, should be considered the mainstay in enamel hardening, because the absorption bands of phosphate, carbonate and hydroxyl groups of enamel and dentin structures are within 9.0 to 11.0 μ region which coincide well with the wavelengths of the CO2 laser ( 8 ).…”
Section: Introductionmentioning
confidence: 99%